The Effect of Optimized Ultrafiltration on Perioperative Pulmonary Function During Cardiopulmonary Bypass in Infants Under 10 kg - Niu, Jianhong; Zhai, Guangdi; Zheng, Aibin; Zhou, Juanying; Jiang, Shengqi; Ma, Jianping (Frontiers in Pediatrics, 2021)
Objective: This study aims to investigate the effect of optimized ultrafiltration on electrolytes, acid-base balance, and pulmonary function during perioperative cardiopulmonary bypass (CPB) in infants with a low body weight (under 10 kg). Methods: A total of 30 children who underwent surgical correction for congenital heart disease in Changzhou Children’s Hospital between January 2018 and December 2019 were randomly divided into two groups. In the treatment group, ultrafiltration pre-treatment was carried out for blood-containing priming fluid prior to CPB. Balanced ultrafiltration was performed during the operation, whereas optimized and modified ultrafiltration were conducted before closing down and extubation. In the control group, traditional balanced ultrafiltration was used during the operation and modified ultrafiltration combination was used before closing down and extubation. Indexes, such as blood gas analysis and electrolytes, were measured during perioperative CPB, and pulmonary function was observed. Results: No deaths were reported in either group. The ventilator-assisted breathing time in the treatment group was shorter than that in the control group (P < 0.05). The indexes of the treatment group were closer to the physiological values, and the concentration of K+, Lac and Glu decreased. The end site of CPB in treatment group was significantly different (P < 0.05) compared with the control group. The Hb and HCT in the treatment group increased (P < 0.01). Alveolar-arterial differences for oxygen (A-aDO2) and respiratory index (RI) increased significantly in both groups after operation. The lung function of the children in the treatment group began to recover earlier than in the control group. In the treatment group, both A-aDO2 and RI at each time point after operation were lower than in the control group (P < 0.05). Conclusion: Optimizing and modifying the traditional ultrafiltration combination method can effectively shorten the traditional modified ultrafiltration time, reduce the adverse impacts of the modified ultrafiltration technique, and improve the lung function of infants after operation.